Are Preoperatively Requested HBsAg Results Followed? - Kayali, Sumeyra; Ari, Nuray; Akbulut, Ayhan; Akbulut, Hatice Handan (Galenos Publ House, 2024)
Objectives: Hepatitis B virus (HBV), hepatitis C virus, and human immunodeficiency virus are the leading blood-borne infections. In our country, these 3 viral serologies are screened in patients scheduled for surgery. Preoperative hepatitis B surface antigen (HBsAg) screening is performed for HBV infection. In this way, patients with this virus can be detected early and receive early treatment. In this study, we aimed to investigate the rate of diagnosis and follow-up of HBV infection in patients with HBsAg positivity during preoperative serologic screening. Materials and Methods: The HBsAg test results of patients directed to the anesthesia policlinic for preoperative preparation by surgical departments within 3 years were screened. Further examinations for HBV infection and the diagnostic status of patients found to be HBsAg-positive for the first time were analyzed. Results: Of the 679 patients with HBsAg positivity during the 3 year study period, 412 (60.7%) had at least one previous HBsAg test in the hospital automation system. HBsAg positivity was detected for the first time in 267 (39.3%) patients. When the status of further examination was analyzed, 220 (82.4%) of 267 patients were classified as no further examination, 14 (5.2%) as incomplete further examination, and 33 (12.4%) as complete further examination. Conclusion: The electronic patient files should be reviewed before HBsAg testing for preoperative serologic screening. HBsAg-positive patients should be directed to relevant specialty physicians for the diagnosis and treatment of HBV infection, and surgical medical science physicians should be made aware of this issue through training. In addition, it is anticipated that the Electronic Screen Alert application, which will guide physicians, will be useful.
Preoperatif İstenen HBsAg Sonuçları İzleniyor mu?
Keywords: HBsAg; HBV; healthcare workers; hepatitis B virus; preoperative serologic screening; virus